Cytoprotective Effect of Liposomal Puerarin on High Glucose-Induced Injury in Rat Mesangial Cells - Lassina Barro; Jui-Ting Hsiao; Chu-Yin Chen; Yu-Lung Chang; Ming-Fa Hsieh (MDPI AG, 2021)
In diabetic patients, high glucose and high oxidative states activate gene expression of transforming growth factor beta (TGF-β) and further translocate Smad proteins into the nucleus of renal cells. This signal pathway is characterized as the onset of diabetic nephropathy. Puerarin is an active ingredient extracted from Pueraria lobata as an anti-hyperglycemic and anti-oxidative agent. However, the poor oral availability and aqueous solubility limit its pharmaceutical applications. The present paper reports the liposomal puerarin and its protective effect on high glucose-injured rat mesangial cells (RMCs). The purity of puerarin extracted from the root of plant Pueraria lobata was 83.4% as determined by the high-performance liquid chromatography (HPLC) method. The liposomal puerarin was fabricated by membrane hydration followed by ultrasound dispersion and membrane extrusion (pore size of 200 nm). The fabricated liposomes were examined for the loading efficiency and contents of puerarin, the particle characterizations, the radical scavenge and the protective effect in rat mesangial cells, respectively. When the liposomes were subjected to 20 times of membrane extrusion, the particle size of liposomal puerarin can be reduced to less than 200 nm. When liposomal puerarin in RMCs in high glucose concentration (33 mM) was administered, the over-expression of TGF-β and the nuclear translocation of Smad 2/3 proteins was both inhibited. Therefore, this study successfully prepared the liposomal puerarin and showed the cytoprotective effect in RMCs under high glucose condition.